Le site de “ Champ Chalatras ” aux Martres-d'Artière (Puy-de-Dôme) et les premiers témoins archéologiques de la viticulture gallo-romaine dans le bassin de Clermont-Ferrand (Auvergne) - Pierre Vallat; Manon Cabanis (Revue Archéologique du Centre de la France)
A rescue excavation was carried out near Clermont-Ferrand at Martres-d’Artière, on the site of “Champ Chalatras” (Auvergne, Puy-de-Dôme) in 2008, on nearly seven hectares (P. Vallat the archaeologist in charge). This archaeological work, conducted on the site of a large Gallo-Roman villa, brought to light (for the first time in Auvergne) a building associated with wine-growing and plantation ditches dating from the last quarter of the 2nd century AD to the beginning of the following century, which proved the presence of vines in the region of Augustonemetum (Clermont-Ferrand), principal site in the Averne estate. Consequently it seems opportune to produce the first documentary results concerning ancient wine-growing in Limagne which are based on the recent archaeological data from 2008 and on the collection of other clues listed during this attempt at summarization (literary sources, archaeological data, ionographic, and botanic archaeology). The state of multidisciplinary knowledge is still limited to the Clermont-Ferrand region, the only Averne area at all documented. The wine-growing map of Gaul has evolved a great deal in the recent years. The recent discoveries from the Clermont-Ferrand region also open a new window on the north-eastern part of the province of Aquitaine.